UN Palermo Protocol's Implementation on the Legal Protection of Street Children Trafficked in Indonesia - Yordan Gunawan; Amarta Yasyhini Ilka Haque; Moli Aya Mina Rahma; Nazella Jeanny Andrian (Jurnal Hukum Novelty, 2022)
Introduction to The Problem: As one of the countries which ratified the UN Protocol to Prevent, Suppress, and Punish Trafficking in Persons, especially Women and Children, Indonesia recognizes the protection of child trafficking. However, the activity of child trafficking is still rampant throughout Indonesia.Purpose/Objective Study: Hence, this research aims to analyze further the implementation of the UN Palermo Protocol on the legal protection of street children trafficked in Indonesia.Design/Methodology/Approach: The research was normative legal research method or qualitative legal research.Findings: According to the findings of the study, as part of the implementation of the UN Palermo Protocol, Indonesia has made significant efforts to combat human trafficking crime through multilateral agreements and cooperation, the establishment of some related services, and the enactment of numerous legal products. Despite the fact that many efforts have been made by Indonesia to address the crime of child trafficking, the law enforcement on the crime of human trafficking in Indonesia is still inadequate. There are still many children on the street who are victims of human trafficking. As a result, we propose that the government enact a specific law or a special supervision system to combat the trafficking of street children in Indonesia.Paper Type: Research Article